Cognitive Style, Global Mindset, Self-Control, and Organizing Capacity of Managers: Insight from Retail Stores - Zainul, Mohammad; Wicaksono, Teguh; Utaya, Yuniar Anggraini (Management Department, Universitas Islam Negeri Alauddin Makassar, Indonesia, 2024)
The increasing demand and lifestyle changes have made shopping centers a primary destination for leisure, driving a surge in visits and compelling tenants to adapt continuously to these changes. However, tenant supervisors vary in their capacity to manage their businesses effectively amid this influx. This study explores how cognitive style, global mindset, and self-control predict organizational capacity in managing businesses in response to current trends. Using an exploratory quantitative design, the PLS-SEM procedure was employed to analyze data collected from 180 tenant leaders at the largest shopping center in Makassar, Indonesia. The findings confirm the significance of all proposed hypotheses, except for the influence of cognitive style on organizational capacity. This research highlights that tenant leaders must develop a strong understanding of global issues and exhibit self-restraint, particularly through an internal locus of control, to navigate ongoing changes effectively.